1989
DOI: 10.1136/bjo.73.8.591
|View full text |Cite
|
Sign up to set email alerts
|

A study of iris melanoma in Northern Ireland.

Abstract: SUMMARY A retrospective study of all cases of iris melanoma in Northern Ireland over a 15-year period was undertaken. A total of 18 cases were identified. Of these, nine were histologically proved to be iris melanomas of various types. Within the period of follow-up two patients died from metastatic deposits. In both cases invasion of the anterior face of the ciliary body was present on histological examination. The implications for management are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…4,[9][10][11][12][13][14][15][16] In 1957 Duke and Dunn published an article on 28 iris melanomas, of which 3 occurred in children, 19 in mid-adults, and 6 in older adults and only one death from metastatic disease. 9 The incidence of iris melanoma has been estimated at 0.4 to 0.6 cases per 1 million persons per year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[9][10][11][12][13][14][15][16] In 1957 Duke and Dunn published an article on 28 iris melanomas, of which 3 occurred in children, 19 in mid-adults, and 6 in older adults and only one death from metastatic disease. 9 The incidence of iris melanoma has been estimated at 0.4 to 0.6 cases per 1 million persons per year.…”
Section: Discussionmentioning
confidence: 99%
“…The following data were extracted from the medical records: patient age at diagnosis (years), sex, race (white, African American, Hispanic, Asian, Native American, Middle Eastern, Asian Indian), location of melanoma (iris only or iris plus ciliary body/ choroid), quadrant location of tumor epicenter (superior, nasal, inferior, temporal, diffuse), clock hour epicenter of tumor (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), largest tumor basal dimension and thickness (mm), tumor configuration [dome, plateau, tapioca (multinodular amelanotic translucent variant)], pigmentation (pigmented, nonpigmented, mixed), intraocular pressure (IOP), secondary glaucoma (neovascular glaucoma, pigmentary glaucoma), tumor seeding in the angle, number of clock hours of tumor seeding, corectopia, ectropion uveae, and extraocular extension. Tumor basal diameter was measured by slit-lamp biomicroscopy and tumor thickness was estimated by slit-lamp biomicroscopy and measured (in more recent years) by ultrasound biomicroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…(BrJ7 Ophthalmol 1995;79: 306-312) The philosophy regarding the management of melanocytic iris lesions has gradually evolved towards more conservative treatment. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In general, a non-growing iris melanocytic tumour is managed by observation, followed by local resection if growth is documented. An iris melanoma that has a diffuse growth pattern and secondary glaucoma is usually managed by enucleation.…”
mentioning
confidence: 99%
“…[2][3][4][5]3 in Denmark, has observed a recent increase in the incidence of these tumours and suggested that the increase in ultraviolet solar radiation might be responsible. In New Zealand solar ultraviolet radiation is high and levels are increasing as a result of depletion of the ozone layer over Antarctica.…”
mentioning
confidence: 99%
“…Also, the numbers of reported malignant tumours are dependent on the pathological classifications employed. [2][3][4][5] While Gislason et al 4 and McGalliard and Johnston 2 described the melanomas as spindle A, B, epithelioid, or mixed, Jensen 3 used spindle, mixed, epithelioid, and naevoid; and Raivio 5 spindle cell and mixed cell types. Lastly, the clinical readiness to excise iris tumours varies from country to country and between surgeons.…”
mentioning
confidence: 99%